Genotypic and phenotypic evidence of T-cell leukemia in a patient successfully treated by interferon-alpha for typical hairy cell leukemia - Knecht, H; Sarraj, A; Delacrétaz, F; Bachmann, E; Clément, F (Leukemia, 1991)
A 53-year-old man was diagnosed to have typical hairy cell leukemia. Immunophenotyping of frozen splenic tissue showed clonality of hairy cells for mu lambda, confirmed by the corresponding immunoglobulin gene rearrangements. The patient was successfully treated with interferon-alpha (IF-alpha). In the fifth year of treatment with IF-alpha the morphology of peripheral blood mononuclear cells (PBMC) and of bone marrow infiltration changed with the appearance of numerous small to intermediate shaped lymphocytes of a T-helper phenotype. Frank leukemia, resistant to IF-alpha treatment and ultimately aggressive chemotherapy, developed. Emergence of this second clonal disease was confirmed by rearrangement studies performed on PBMC; rearrangements of both alleles of the TCR beta were identified, whereas the JH and lambda IVS genes were in germline configuration. The outgrowth of a second, malignant T-cell clone paralleled by the disappearance (down-regulation?) of the initial B-cell clone while under cytokine treatment is consistent with the possibility that IF-alpha favoured the emergence of this second clone.